C++ data structures and algorithm design principles : Leverage the Power of Modern C++ to Build Robust and Scalable Applications - Carey, John; Doshi, Shreyans; Rajan, Payas (Packt Publishing, 2019)
C++ is a mature multi-paradigm programming language that enables you to write high-level code with great control over the hardware. This book updates your working knowledge of modern C++ by showing how you can use algorithms and data structures to build scalable, efficient modern applications.